(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
Electronic banking plays a prominent role in providing the best banking services and upgrading the banking sector for the better, so this study aimed to shed light on the most prominent obstacles that prevent the application of electronic banking in banks operating in the city of Nasiriyah, and in order to achieve this goal the researcher used the descriptive analytical approach And through a questionnaire form that was distributed to a group of employees, numbering (60) employees in the upper, middle and operational departments in a number of branches of private banks operating in the city of Nasiriyah, namely (the Iraqi Trade Bank, the Gulf Commercial Bank, the Bank of Baghdad, the Union Bank of Iraq), which represented The study sample, (50) valid forms were retrieved for analysis, After the study and analysis of the paragraphs of the questionnaire, a set of results was reached, the most important of which was that the cultural and social environment was one of the most prominent obstacles to the application of electronic banking in the branches of banks operating in the city of Nasiriyah. The focus of the questionnaire form.